2012
DOI: 10.1177/160940691201100201
|View full text |Cite
|
Sign up to set email alerts
|

Ethical Dilemmas of a Clinician/Researcher Interviewing Women who have Grown up in a Family Where There was Domestic Violence

Abstract: This paper attempts to illuminate some of the ethical dilemmas of a clinician/researcher interviewing women about a sensitive topic-their experience of having witnessed domestic violence in the family they grew up in, as part of a grounded theory study. Vignettes are presented to illustrate the self-reflexive process of the researcher and how she understood the effects of the interview process on her and the participants. The authors argue that doing indepth qualitative research interviewing is an intervention… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
2
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 55 publications
1
13
0
Order By: Relevance
“…Johnson and Benight (2003);Newman, Walker, and Gefland (1999);and Walker, Newman, Koss, and Bernstein (1997) report similar results from similar studies. In agreement with Scerri et al (2012), the case studies presented here suggest that skilfully conducted qualitative interviews can be, and often are, a positive intervention in the lives of study participants; they give study participants an opportunity to off-load and to obtain the benefits of talking through their thoughts with an empathetic other. Future research should incorporate rigorous investigation of this suggested benefit as these reported benefits are often collected through informal, ad-hoc follow-up conversations.…”
Section: Discussion: Benefitting From Research and Mitigating Risksupporting
confidence: 82%
See 1 more Smart Citation
“…Johnson and Benight (2003);Newman, Walker, and Gefland (1999);and Walker, Newman, Koss, and Bernstein (1997) report similar results from similar studies. In agreement with Scerri et al (2012), the case studies presented here suggest that skilfully conducted qualitative interviews can be, and often are, a positive intervention in the lives of study participants; they give study participants an opportunity to off-load and to obtain the benefits of talking through their thoughts with an empathetic other. Future research should incorporate rigorous investigation of this suggested benefit as these reported benefits are often collected through informal, ad-hoc follow-up conversations.…”
Section: Discussion: Benefitting From Research and Mitigating Risksupporting
confidence: 82%
“…Qualitative interviews -the cornerstone of many social research studies exploring IPV -have been discussed as a positive intervention by previous researchers (Scerri, Abela, & Vetere, 2012). Griffin, Resick, Waldrop, and Mechanic (2003) investigated the effects of taking part in interviews among domestic violence survivors and found that the vast majority bore no ill effects from the experience, and most described it as a positive experience.…”
Section: Discussion: Benefitting From Research and Mitigating Riskmentioning
confidence: 99%
“…It was therefore sometimes difficult not to be drawn into their relationships and to feel affected by their struggles, and the violence and abuse they had experienced. Other researchers have discussed vicarious trauma after listening to participants' traumatic and unsettling accounts (Love et al, 2019;Sammut Scerri et al, 2012;Van der Merwe & Hunt, 2019). In this study, researchers were offered regular (group and individual) clinical supervision by a clinical psychologist to process the emotions they experienced from hearing these stories.…”
Section: Researchers' Felt Experiences Of Interviewingmentioning
confidence: 99%
“…If interviewing a child, debrief afterwards to help them differentiate the real and experimental situations that the interview discussed. (41,56,72) X X…”
Section: Safetymentioning
confidence: 99%